Study of Some Virulence Factor and Detection of Sortase Enzymes A and Cov R/S of Streptococcus Agalactiae by PCR - Faaz Nassir AL-Saad, Nktel (Al-Qadisiyah Journal of Pure Science, 2018)
This study included 100 pregnant and non-pregnant patients infected with vaginitis who were attended the hospital of maternity and children in Babylon province from January to May 2016. Only 25 isolates of Streptococcus agalactiae (GBS) were isolates. Sortase A enzyme were detected by using specific primer for PCR techniques and also found that all GBS strain have sortase A enzyme, so this enzyme is consider as housekeeping enzyme. Moreover, specific PCR primers were used for detection of CovR/S enzymes. It was found that CovR/S was observed only in tow isolates of Group B streptococcus GBS strains. The isolates have been examined to chick their ability to produce colonization factor antigens type1 (CFA/I) . The finding showed that they revealed the ability to produce CFA/1 in the existence of D-mannose and Vancomysin. Also, the isolates, have the ability to produce CFA/1 in the existence of D-mannose without Vancomysin. The capability of GBS isolates to produce Hemolysin in the presence of Vancomysin were studied. It was found that there was no hemolysis in the presence of Vancomysin (except for one isolate), this will give good sign for this antibiotic to reduce the ability of this bacteria to obtain iron from environment.